2018
DOI: 10.3389/fphys.2018.01154
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Transcriptomic and microRNAomic Profiling Reveals Immune Mechanism for the Resilience to Soybean Meal Stress in Fish Gut and Liver

Abstract: In aquafeeds, fish-meal has been commonly replaced with plant protein, which often causes enteritis. Currently, foodborne enteritis has few solutions in regards to prevention or cures. The recovery mechanism from enteritis in herbivorous fish may further help understand prevention or therapy. However, few reports could be found regarding the recovery or resilience to fish foodborne enteritis. In this study, grass carp was used as an animal model for soybean meal induced enteritis and it was found that the fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 85 publications
(101 reference statements)
3
36
0
Order By: Relevance
“…Inflammation are protective responses to eliminate the initial cause of cell injury and initiate tissue repair, in which inflammatory cytokines play vital roles (Karin and Clevers, 2016). Wu et al (2018) found that grass carp showed upregulated pro-inflammatory cytokine (IL17) and anti-inflammatory cytokine (IL10) expression during the wound healing stage whereas all down-regulated in the recovery stage both in liver and gut. Wei et al (2019) also reported that failed inflammatory response is a key reason for the severe damage in spiral valve intestine of Amur sturgeon.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation are protective responses to eliminate the initial cause of cell injury and initiate tissue repair, in which inflammatory cytokines play vital roles (Karin and Clevers, 2016). Wu et al (2018) found that grass carp showed upregulated pro-inflammatory cytokine (IL17) and anti-inflammatory cytokine (IL10) expression during the wound healing stage whereas all down-regulated in the recovery stage both in liver and gut. Wei et al (2019) also reported that failed inflammatory response is a key reason for the severe damage in spiral valve intestine of Amur sturgeon.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, soybean meal, which is considered one of the most hopeful candidates for fish meal replacement, can partially or fully replace the fish meal but introduces many anti-nutritional factors. Consequently, fish enteritis induced by plant proteins has become one of the main challenges for sustainable aquaculture (2), and this occurs in a dose-dependent manner (1,3).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies of miRNAome in turbot intestinal function have reported that miRNAs contributed to the intestinal immune responses, preventing host infection, which the potential target genes of differentially expressed miRNAs were involved in multiple functional categories, including the RIG-I signaling pathway, immune defense/evasion, the toll-like receptor signaling pathway, and inflammatory responses (23). Also, it was found via small RNA sequencing that fish diet could affect the expression of intestinal miRNAs and target genes and immune-related pathways, including cell adhesion molecules, ECM-receptor interaction, the apoptosis signaling pathway, cytokine-cytokine receptor, and the VEGF signaling pathway (3,24). However, there has been a lack of investigation of the underlying immune response by combining both transcriptomes and small RNA sequencing, and this requires further elucidation, especially in carnivorous fish.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mRNA samples used for transcriptome sequencing were also subjected to realtime quantitative RT-PCR validation (n = 3), following a previously published protocol [14,16]. After RNA isolation, reverse transcription and quantitative PCR (qPCR) experiments were carried out for 11 genes.…”
Section: Validation Through Reverse Transcription-polymerase Chain Rementioning
confidence: 99%